Pengembangan Aplikasi Berbasis Web untuk Pengelolaan Manajemen pada Sekolah Annajah - Arbiansyah, Farid; Hugeng, Hugeng; Sutrisno, Tri (STMIK Banjarbaru, 2024)
The management of the academic administration management system at the MA Annajah school which is still managed manually causes the academic administration process as well as the delivery and access of academic information for all parties related to the school to be ineffective. This research aims to develop a Web-based application to assist MA Annajah school management in managing academic administration, as well as as a means of communicating and conveying information to all stakeholders effectively. The research uses the stages in the Waterfall development model. Some of the functional features presented in the application include processing student data, teacher data, subject data, and student grade data. System design uses Object-oriented tools (UML/Unified Modeling Language), while implementation uses PHP and CSS programming languages. Testing system functionality using Blackbox testing techniques. The test results show that all functional features that have been developed can run validly.Keywords: Academic management; Information Technology; Web-basedÂ AbstrakPengelolaan sistem manajemen administrasi akademik pada sekolah MA Annajah yang masih dikelola secara manual menyebabkan proses administrasi akademik serta penyampaian dan akses informasi akademik bagi seluruh pihak yang terkait dengan sekolah menjadi tidak efektif. Penelitian ini bertujuan untuk mengembangkan aplikasi berbasis Web untuk membantu pihak manajemen sekolah MA Annajah dalam mengelola administrasi akademik, serta sebagai sarana komunikasi dan penyampaian informasi bagi seluruh stakeholder secara efektif. Penelitian menggunakan tahapan-tahapan dalam model pengembangan Waterfall. Beberapa fitur fungsionalitas yang disajikan pada aplikasi meliputi pemrosesan data siswa, data guru, data mata pelajaran, serta data nilai siswa. Desain sistem menggunakan tools berorientasi Objek (UML/Unified Modeling Language), sedangkan implementasi menggunakan bahasa pemrograman PHP dan CSS. Pengujian fungsionalitas sistem menggunakan teknik pengujian Blackbox. Hasil pengujian menunjukkan seluruh fitur fugsional yang telah dikembangkan dapat berjalan secara valid.Â